INTERACTIVE COOPERATION CRISIS MANAGEMENT ON THE BASIS OF SIGNALS - I. V. Gladkov (Модернизация, инновация, развитие)
Foreign experience shows that the processes of interactive cooperation in the field of crisis management can be developed using a variety of resources. Scientific interest is a method based on the signals provided by means of which a prediction of crisis.